Multi-segment osteotomy with interlocking intramedullary nail fixation in the treatment of lower limb deformity in older children with hypophosphatemic rickets - Ming Lu; Haifeng You; Yukun Wang (Frontiers Media S.A., 2024)
ObjectiveMalformations of the lower limbs caused by hypophosphatemic rickets in older children are mostly complex, occurring on multiple planes without a single apex and showing arcuate bending of the diaphysis combined with torsion deformity, and are difficult to correct. This study retrospectively investigated the effect of and indicators for multi-segment osteotomy with interlocking intramedullary nail fixation in the treatment of bony deformity caused by hypophosphatemic rickets.MethodsThe clinical data of 21 hypophosphatemic rickets patients seen between August 2007 and March 2022 were collected. The age range of the patients at the first surgery was 11 years and 1 month old to 15 years and 3 months old, with an average age of 12 years and 8 months. There were 6 males and 15 females. All patients had abnormal alignment of their lower limbs, with 32 limbs having varus deformity and 10 limbs having valgus deformity.ResultsA total of 67 surgeries were performed across the 21 patients, including 24 cases of femoral osteotomy with antegrade intramedullary nail fixation, 6 cases of femoral osteotomy with retrograde intramedullary nail fixation, and 20 cases of tibial osteotomy with interlocking intramedullary nail fixation. A total of 34 limbs eventually underwent interlocking intramedullary nail fixation, 9 with genu valgum and 25 with genu varus. All 21 patients were followed up for a period of 14∼96 months, with an average of 42.6 months. The ends of the osteotomies achieved bony union in 4-9 months (average 6.8 months), after which normal weight-bearing walking could be resumed. No infection, vascular or neurological complications, or nonunion occurred. During postoperative follow-up, the alignment the lower limbs passed through zone 1 in 13 limbs, zone 2 in 12 limbs, and zone 3 in 5 limbs. The overall rate of an excellent effect was 83.3%.ConclusionFor lower limb deformity caused by hypophosphatemic rickets in older children, multi-segment osteotomy and strong fixation with interlocking intramedullary nails can achieve good correction outcomes.